2021
DOI: 10.3233/wor-213568
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study of employers’ and employees’ evaluations of job seekers with a mental illness, disability, or of a cultural minority

Abstract: BACKGROUND: Groups in society that are under-represented in the workforce encounter various barriers in the job-seeking process. Some of these barriers are found on the employer’s side of the table. OBJECTIVE: This study investigates supervisors’ and employees’ assessments of job seekers with different forms of disabilities, health issues, or with a minority background. It also investigates respondents’ previous experience with such colleagues, and whether supervisor status affects their assessments. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…There is a stigma around mental illness, which is often considered to be due to a lack of knowledge about mental illness. This constitutes a basis for poorer treatment [1]. This, in turn, constitutes a basis for poorer treatment [1,2].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is a stigma around mental illness, which is often considered to be due to a lack of knowledge about mental illness. This constitutes a basis for poorer treatment [1]. This, in turn, constitutes a basis for poorer treatment [1,2].…”
Section: Introductionmentioning
confidence: 98%
“…This constitutes a basis for poorer treatment [1]. This, in turn, constitutes a basis for poorer treatment [1,2]. Adolescents and young adults hold stigmatizing beliefs about mental health treatments, health professionals, and access to care.…”
Section: Introductionmentioning
confidence: 99%
“…Besides a large body of research concerned with identifying barriers in the labor market, for example disability-related prejudice in society [ 5 ] and bias in employers’ hiring decisions [ 6 ], scholars have emphasized work inclusion as a conceptual point of departure for understanding processes that lead to marginalization as well as opportunities for participation [ 7 ]. The concept of work inclusion has been developed in relation to the more general concept of social inclusion and considers individuals’ opportunities to participate in society on a basis of respect for difference.…”
Section: Introductionmentioning
confidence: 99%
“…They found that blind people and people with mental disabilities experience most barriers in recruitment. Fyhn et al (2021) include various disadvantaged groups in their FSE and examine the likelihood of Norwegian supervisors and employers hiring different applicants. The results show that the likelihood of hiring an applicant with a physical or mental disability is significantly lower compared to applicants without any disabilities.…”
Section: Employers' Self-reported and Actual Recruitment Practice In ...mentioning
confidence: 99%